Rules for the design and installation of piling (known as the SAA Piling Code) (SA, 1978)
Establishes rules for the design and installation of timber, steel, concrete and cast iron piles. A section dealing with load tests is included. Extensive notes and appendices are included dealing with recommended methods for design calculations, safe working practices and durability of piles. It excludes sheet piles and patented piles